- The Impact of Economic and Efficiency Ratios on the Effectiveness of Bandung City's Financial Performance (2011–2024) - Almeira, Gianina; Kurniawati, Cahya; Kamiela, Intan; Ratuarat, Mercy (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2025)
This research aims to analyze the extent to which the economic ratio and budget efficiency ratio impact the effectiveness of the Bandung City Government’s performance during the period from 2011 to 2024. The primary focus of this study is to quantify the influence of these two ratios on the government’s capability to manage the budget effectively. Employing a quantitative methodology, multiple linear regression analysis was conducted on secondary data sourced from budget realization reports spanning 2011 to 2024. The results reveal that the economic ratio exerts a statistically significant negative effect on effectiveness, whereas the efficiency ratio does not demonstrate a significant impact. Collectively, both variables significantly influence performance effectiveness, although their combined contribution accounts for only 37.4 percent of the variation in effectiveness. These findings suggest that efficient budget management does not significantly affect the effectiveness of financial reporting, while a higher economic ratio negatively correlates with overall effectiveness. This study is novel in that it directly investigates the influence of economic and efficiency ratios on financial effectiveness in local government reporting, a topic rarely explored in previous research.